(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In recent years, a number of measures have been implemented in our country to protect the mother nature and preserve biological species. Tourism has become a direction that has a special place in the service sector. Therefore, the increase and development of the directions of this sector will create an opportunity for the economic growth of the country by increasing the export of services.